Finite element method for analyzing effects of porous baffle on liquid sloshing in the two-dimensional tanks. Issue 5 (15th October 2020) - Gao, Hangduo; Yin, Zhao; Liu, Jun; Zang, Quansheng; Lin, Gao
Abstract : Purpose: The purpose of this paper is to analyze the liquid sloshing behaviors in two-dimensional tanks with various porous baffles under the external excitation. Design/methodology/approach: Adopting the finite element method (FEM) and control variable method to study the impacts of the height, length, number, location, shape, porous-effect parameter of the porous baffle, the external load frequency and the shape of the tank on the liquid sloshing response. Findings: The amplitude of the free surface can be reduced effectively when the baffle opening is appropriate. The anti-sway ability of the system increases in pace with the baffle's height growing. Under the same conditions, the shapes of the baffles have an important effect on improving the anti-sway ability of the system. Originality/value: As there exist the differences of the velocity potential between each side of the porous baffle, which means that there are two different velocity potentials at a point on the porous baffle, the conventional finite element modeling technologies are not suitable to be applied here. To deal with this problem, the points on the porous baffle are regarded as two nodes with the same coordinate to model and calculate.